Gender and Immigration: Double Negative Effects in the Labor Market Outcomes of University Graduates in Germany? - Guido Bünstorf; Stefan Krabel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Survey data for a large sample of recent graduates from 37 German universities are used to study labor market outcomes of highly skilled young women and immigrants. Our results indicate a systemic wage gap for women, but not for male immigrants. We find no evidence that female immigrants suffer from a double-negative effect of being disadvantaged twofold (in terms of gender and immigration status). Similar patterns are obtained for job satisfaction and the match quality of competences and job requirements.
Keywords: J71; J61; I23; 330